Efektivitas krim ekstrak daun melinjo (Gnetum gnemon L.) terhadap jumlah sel fibroblas pada luka bakar derajat II dalam tikus putih (Rattus norvegicus) - Sulaiman, Azhari Athaillah; Maslachah, Lilik; Utama, Suzanita; Yuniarti, Wiwik Misaco; Sukmanadi, Moh.; Hidajati, Nove (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Burn wound is an injury that causes tissue damage, typically due to contact with a heat source. Fibroblasts have an important role in wound healing, synthesizing collagen as the main constituent of the extracellular matrix which is important in wound integrity. The purpose of this study was to determine the effectiveness of cream of melinjo (Gnetum gnemon L.) leaf extract on the number of fibroblast cells in deep partial thickness burn in white rats (Rattus novegicus). Twenty male white rats (Rattus norvegicus) were divided into five treatment groups, with four replications in each group, and were induced with in deep partial thickness burn. The negative control group (K-) was treated with cream base, the positive control group (K+) was treated with Silver Sulfadiazine, while P1, P2, and P3 group was treated with respectively 2.5, 5 and 10% melinjo (Gnetum gnemon L.) leaf extract cream. Therapy was given twice a day for 14 days. Oneway ANOVA showed significant differences between each treatment group (p <0.05) and continued with the Duncan test. The average number of fibroblasts in each treatment group showed that the K- were significantly different from the K+, P2, P3 groups but not P1. The lowest mean number of fibroblast cells was found in the K- group. The conclusion from the research that has been carried out was that melinjo (Gnetum gnemon L) leaf extract cream decrease the number of fibroblast cells in second-degree burns wounds in white rats (Rattus norvegicus).